2020
DOI: 10.1007/s42242-020-00085-5
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinted breast tumor model for structure–activity relationship study

Abstract: In this paper, we present a 3D printed tumor spheroidal model suitable for drug discovery. This model is based on a hydroxyethyl cellulose/alginate/gelatin (HCSG) composite biomaterial that has three distinct properties: (1) the HCSG is similar to the commercial basement membrane extract in Ki67, MUC1, and PARP1 expressions of MCF-7 cells for embedding culture; (2) the HCSG is printable at room temperature; and (3) the HCSG can be large-scale manufactured at an ultralow cost.We printed a 3D MCF-7 spheroid mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This result was consistent with the report that different densities of cells resulted in different spheroid sizes, and the spheroid area of cells at the density of 45,000 cells/well turned out to be 6.0 × 10 6 μm 2 [ 54 ]. Reports showed that the size of tumor spheroids could be controlled at around 200 μm after 7 to 8 days when grown in microwells, which was the largest [ 55 , 56 ]. In this study, the size of the tumor sphere increased from day 3 to day 21, indicating that the platform simulated the process of tumor formation more realistically.…”
Section: Resultsmentioning
confidence: 99%
“…This result was consistent with the report that different densities of cells resulted in different spheroid sizes, and the spheroid area of cells at the density of 45,000 cells/well turned out to be 6.0 × 10 6 μm 2 [ 54 ]. Reports showed that the size of tumor spheroids could be controlled at around 200 μm after 7 to 8 days when grown in microwells, which was the largest [ 55 , 56 ]. In this study, the size of the tumor sphere increased from day 3 to day 21, indicating that the platform simulated the process of tumor formation more realistically.…”
Section: Resultsmentioning
confidence: 99%
“…A proof-of-concept study utilizing bioprinted breast cancer constructs was reported by Li et al. [136] . Using a hydroxyethyl cellulose/alginate/gelatin hydrogel and MCF-7-based spheroid bioprinted construct, the anti-breast cancer activity of phosphoramidates (13 amino acid-containing flavone) was examined and the results indicated that alanine structure induced a stronger drug resistance than phenylalanine in the MCF-7 cells.…”
Section: Cancer-specific Bioprinted Models For Precision Chemotherapymentioning
confidence: 99%
“…The high diversity of chemical structures and properties of these plant polysaccharides opens the possibility for their application in several fields, including in the food area (e.g., as gelling agents) [ 97 ], in the biomedical field (e.g., in drug delivery systems) [ 98 ], and, more recently, in tissue engineering [ 99 ]. The interest in using some of these plant-derived polysaccharides in the formulation of bioinks for 3D bioprinting applications has also grown considerably in the later years, as summed up in Table 2 , with several works using cellulose and nanocelluloses [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ] and pectin [ 119 , 120 ].…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…The use of cellulose derivatives for the development of bioinks has been recently reviewed [ 126 , 127 ], and it is mainly focused on the exploitation of CMC. However, other cellulose derivatives, such as methyl cellulose [ 101 ], hydroxyethylcellulose [ 112 ], and hydroxypropyl methyl cellulose [ 113 , 114 ], are also starting to be studied in this context. For instance, Ni et al [ 114 ] mixed silk fibroin with hydroxypropyl methyl cellulose, that was previously methacrylated, in different proportions (3:1, 2:2 and 1:3) to bioprint, through extrusion, bone marrow-derived mesenchymal stromal cells (BMSC)-laden double network hydrogels for cartilage tissue repair, as seen in Figure 3 A.…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%